2016
DOI: 10.4017/gt.2016.15.1.008.00
|View full text |Cite
|
Sign up to set email alerts
|

Mobiles for mobility: Participatory design of a ‘Happy walker’ that stimulates mobility among older people

Abstract: O r i g i n a l Mobiles for mobility: Participatory design of a 'Happy walker' that stimulates mobility among older peopleThe mobility of older adults is seen as a fundamental prerequisite for independent living and societal participation. We define mobility as going outdoors and travel to reach people and places, such as going for walks, visiting friends, shopping and attending cultural events. Being mobile leads to psychological benefits of going out, in particular reduction of feelings of loneliness and ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Beyond identifying needs, various papers also note that involving older people helped designers to better learn about older people’s lives. Many studies indicate that involving older people raised their awareness of older people’s daily life practices and activities, such as the importance of social connections ( Mehrrotra et al, 2016 ), common routines for housekeeping ( Verhoeven, Cremers, Schoone, & Dijk, 2016 ), medical practices ( Pater, Owens, Farmer, Mynatt, & Fain, 2017 ), and family visits ( Leong & Johnston, 2016 ). Relatedly, some studies report that the involvement of older people contributed to a better understanding of the lives of older people to the extent that it altered stereotypes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond identifying needs, various papers also note that involving older people helped designers to better learn about older people’s lives. Many studies indicate that involving older people raised their awareness of older people’s daily life practices and activities, such as the importance of social connections ( Mehrrotra et al, 2016 ), common routines for housekeeping ( Verhoeven, Cremers, Schoone, & Dijk, 2016 ), medical practices ( Pater, Owens, Farmer, Mynatt, & Fain, 2017 ), and family visits ( Leong & Johnston, 2016 ). Relatedly, some studies report that the involvement of older people contributed to a better understanding of the lives of older people to the extent that it altered stereotypes.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, we also found multiple studies that cast doubt on the positive impact of older adults’ involvement on acceptance. These studies report how older people indicate some positive attitudes to the developed design but provide suggestions for additional features (e.g., Gorkovenko et al, 2017 ; Guo et al, 2016 ; Verhoeven et al, 2016 ), or use it differently than originally intended ( Leong & Johnston, 2016 ; Eftring & Frennert, 2016 ; Nielsen et al, 2018 ). Other studies even identified instances of low acceptance.…”
Section: Resultsmentioning
confidence: 99%
“…• Lack of literature on co-creation governance and frameworks [53] • Requiring participants to complete interventions before participating in co-design [68] • Complexity of data collection measures [36] • Combining appreciative action and reflection, or an integrated knowledge translation approach with normalization process theory [50,62] • User experience honeycomb model [43] • Participatory action research [51] • Photo-elicitation [69] • Training workshop and focus group facilitators in co-creation [52] • Fieldwork tasks [53] • Involving participants early, frequently, and throughout various stages [55,59] Logistics • Open-ended questions [60] • Novice facilitators [60] • Hypothetical scenarios [39,60] • Strategies to ensure members who belong to minority or socially disadvantaged groups are time intensive [57] • Role and workshop aim clarification [53,55,62] • Debrief sessions for facilitators [62] • Sharing workshop summaries with participants [43,52] • Utilizing community organizations or creating community advisory boards to assist with recruitment [51,57] • Formal committee name and constitution [56] Relationships • Time and resources required to build trust within community of interest [57] • Bias arises from a desire to please and maintain group dynamics [36,46] • Participatory Action Research approach may create a power differential [51] • Seniors require longer interviews [36] • Building group dynamics (meeting in person, allowing time to socialize, and demonstrating appreciation for participation) [38,55,59] Participation • Fatigue/loss of concentration…”
Section: Framework and Methodologiesmentioning
confidence: 99%
“…• The Groningen Activity Restriction Scale (GARS) has been applied in several studies in the Netherlands. It has proven to be a very useful instrument: it makes it possible to (1) describe more precisely the severity of the disablement caused by several chronic conditions, (2) establish changes in disablement over time, (3) differentiate more accurately between degrees of disability, and (4) improve the assessment of the need for professional care 30 . The GARS consists of 18 items and 5 response categories.…”
Section: F O X H U N T I N G G a M E F O R M O B I L I T Ymentioning
confidence: 99%
“…With increasing age, the possibility exists for a progressive decline in physical function what can lead to problems with regard to daily activities1. Especially among communitydwelling older adults, moving in-and outdoors is a fundamental prerequisite for taking care of daily activities, for independent living and social participation 2,3 . The frequency of going outdoors is a good indicator of functional and psychosocial functioning among community-dwelling older adults 4 .…”
Section: Introductionmentioning
confidence: 99%